Implementation of Istishna Accounting Based on PSAK 404: Challenges and Implications for Sharia Banking in Indonesia - Mila Ari Sri Mulyani; Iwan Setiawan (Aktiva)
Purpose: This study aims to analyze the conformity of istishna accounting implementation with the applicable standards, identify the challenges faced in the implementation process, and analyze the implications of the implementation. Design/methodology/approach: This study uses a qualitative approach with descriptive methods based on secondary data. Research Findings: The findings in this study show that most Islamic Banks in Indonesia generally implement PSAK 404 quite well. However, the implementation still faces several challenges, including difficulties in applying the precentage of completion method, the complexity of recording istishna accounting, and the lack of understanding related to PSAK 404. In addition, the implementation of PSAK 404 also has a positive impact, such as increasing transparency and accountability of financial statementst, increasing operational efficiency, and strengthening the competitive position of Islamic Banking in the global market. Contribution/Originality/Novelty: This study provides new insights into the challenges and implications in the implementation of PSAK 404.